Das Gründungsgeschehen in Dresden, Rostock und Karlsruhe: eine Betrachtung des regionalen Gründungspotenzials - Tobias Henning; Pamela Mueller; Michael Niese (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
This paper compares the structure and the development of new firm formation activity in three German regions. The two East German regions, Dresden and Rostock, show significantly higher start-up rates than the West German region Karlsruhe. The analysis of entry cohorts reveals that not only the direct employment effects are more pronounced in Karlsruhe but also the probability of failure is significantly lower in Karlsruhe compared to the two East German regions. The regional potential for innovative new firms is measured by the number of natural scientists and engineers in high-tech industries and public science organizations. This potential is underdeveloped in Rostock while Dresden almost caught up with Karlsruhe. Policy-sponsored networks aiming to increase the number of innovative start-ups exist in all three regions. Dresden and Karlsruhe have successfully launched a considerable number of university start-ups.
Keywords: M13; O3; O18; R11; 330; Entrepreneurship; new firm formation; entry cohorts; East Germany; research and development; innovation; high-tech industries; start-up promotion; EXIST